Life of fire : mastering the arts of pit-cooked barbecue, the grill, and the smokehouse - Martin, Pat, 1972-; Fauchald, Nick (Clarkson Potter/Publishers, 2022)
"From one of the South's most acclaimed pitmasters comes the definitive guide to open-fire cooking, from hot coals and roaring flames to warm embers and cold smoke. Nashville's Pat Martin has grown a nine-location-and-counting empire of Martin's BBQ Joints on the strength of his West Tennessee whole hog that is slow-smoked all day and night. One of only a handful of remaining practitioners of this art, Pat didn't come to barbecue as a family heir of legacy recipes; rather, he stumbled into the pit as a somewhat lost student and found the life by the fire to be the one that made the most sense to him. More than his barbecue expertise, Pat's love of open-fire cooking drives this cookbook of how to work with fire in all the stages of its life cycle. Through beautiful photography and detailed instruction, he shows us how to char vegetables on the wild flames of an adolescent fire; how to grill meats on mature coals; how to barbecue shoulders and ribs and, yes, a whole hog on "adult" embers; and finally how to build and use a cold-smoker for hams and bacon. Learn the stages of the fire and you can master Whole Chicken with Alabama White Sauce, Pork Belly Sandwiches, and Open-Pit Spare Ribs, as well as beautiful vegetable-based dishes--Grilled Carrots with Sorghum and Buttermilk, Open-Face Grilled Tomato Sandwiches, Creamed Grilled Corn, and Ash-Roasted Sweet Potatoes--that will transform the way you cook"--